Le maya q'atzij = our Maya word : poetics of resistance in Guatemala - Keme, Emil' (Indigenous Americas., 2021)
"Bringing to the fore the voices of Maya authors and what their poetry tells us about resistance, sovereignty, trauma, and regeneration"--